PROPOSED PSYCHOLOGICAL COUNSELING PROGRAM TO DEVELOP SOCIAL SUPPORT AMONG SHY STUDENTS IN ENGAGING IN SPORTS ACTIVITIES - Sami Yasser, Zaid; Fadel Abbas, Diaa (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The study aims to examine its various aspects and delve into its components to find ways to help students break free from the social isolation induced by their shyness, leading to genuine interactions with others. This can be achieved by developing solutions, including the use of a scale for measuring shyness and social support, aiming to encourage students to engage with their peers and develop a healthier, more confident approach to social interactions. The research problem lies in understanding the type of shyness experienced by the selected group of students and how to overcome it when engaging in sports activities. Since there is no established scale for measuring shyness related to these activities, the researcher intends to use an existing shyness scale and develop a psychological counseling program to address this issue. The research population was defined as first-year students at the College of Physical Education and Sports Science at the University of Kufa, totaling 85 students. The comprehensive sampling method was used to select the sample. The researcher determined the exploratory sample of 10 students, the sample for the scale preparation of 75 students, and the main experiment sample of 30 students, with 15 students in both the control and experimental groups. After applying the scale and collecting information, the data was processed statistically to reach the most important results, in light of which the most important conclusions were built, including:1. The counseling program had a positive effect on the development of social support according to the sessions included for shy students.2. The prepared counseling program effectively addressed the psychological problems faced by students, particularly in the therapeutic aspect for shy first-year students.